Alternative treatment for proximal suspensory desmitis in the hind limb: retrospective study in seven horses - TYRNENOPOULOU (Π. ΤΥΡΝΕΝΟΠΟΥΛΟΥ), P.; DIAKAKIS (Ν. ΔΙΑΚΑΚΗΣ), N. (Journal of the Hellenic Veterinary Medical Society, 2017)
Proximal suspensory desmitis (PSD) has become a frequently diagnosed condition commonly affecting athletic horses. In this study, seven horses with PSD in a pelvic limb were included. Definitive diagnosis was based on clinical signs, results of local anesthesia and ultrasonographic and radiographic examination. Following the initial anti-inflammatory treatment, PSD was treated with an alternative, minimally invasive method, including series of periligamentous injections containing mepivacaine hydrochloride, heparin sodium, a preparation containing natural ingredients and deproteinised haemoderivative of calf blood. Depending on the severity of each case, all horses returned to full work after 8 to 12 weeks.